Environmental customer demands and (forest) governance: evaluating market relations, knowledge networks and positionalities. Issue 1 (2nd January 2018) - Albrecht, Moritz
ABSTRACT: Framed by the debate on the privatization of transnational forest governance and the integration of environmental aspects into economic geography, this study employs a relational conceptualization of governance spaces to evaluate aspects of environmental business customer demands on transnational wood processing corporations. The role of forest certification systems on forest governance is critically discussed, as are inter-firm relations and networks of knowledge production concerning sustainable forest management. A case study of four transnational Finnish corporations is employed to display how environmental aspects of resource exploitation are negotiated by various actors and networks along value chains from producers to European core markets. The role of environmentally focused knowledge networks in environmental governance is stressed. The case study is based on qualitative data (in the form of interviews) gathered from representatives of the respective corporations and other forest governance actors. While forest certification systems are acknowledged as an important driver, this study argues that other real and perceived external relations between actors, institutions and resource areas play a more important role in transnational forest governance than most of the current literature on 'market-driven forest governance' suggests.